Thinking past terror : Islamism and critical theory on the left - Buck-Morss, Susan (Verso, 2006)
Renowned critical theorist Susan Buck-Morss argues convincingly that a global public needs to think past the twin insanities of terrorism and counter-terrorism in order to dismantle regressive intellectual barriers. Surveying the widespread literature on the relationship of Islam to modernity, she reveals that there is surprising overlap where scholars commonly and simplistically see antithesis. "Thinking Past Terror" situates this engagement with the study of Islam among critical contemporary discourses-feminism, post-colonialism and the critique of determinism. Reminding us powerfully that domination and consensus are maintained not by the lack of opposing ideas but by the disorganization of dissent, "Thinking Past Terror" presents the empowering idea of a global counter-culture as a very real possibility. If the language of a global, radically cosmopolitan Left is not presumed but its attainment struggled for, if the Leftist project is itself this struggle, then democracy defines its very core.